Tightness-Looseness and Government Innovation Emphasis: Effects on Regional Innovation Outcomes in China - Yutong Li (Journal of Social Computing)
This study examines the interplay between government-level tightness-looseness, cultural tightness, innovation emphasis, and their effects on innovation outcomes in China from 2002 to 2022. Using a panel dataset of government annual reports from 31 provinces, we measured government-level tightness-looseness and innovation emphasis through computational text analysis. Our results show that government tightness consistently hindered radical innovation, while innovation emphasis negatively impacted general and incremental innovation, with no significant effect on radical innovation. The 2014 “Mass Entrepreneurship and Innovation (MEI)” campaign significantly reshaped these dynamics: post-campaign, government tightness exhibited more positive effects on innovation outcomes compared to pre-campaign levels, while looseness became detrimental. Further, the study disentangles the effects of government-level and cultural tightness. Notably, misalignment between government and cultural tightness initially promoted innovation but proved detrimental post-campaign. Similarly, cultural tightness shifted from enhancing to reducing the effectiveness of innovation emphasis after MEI. Robustness tests and mediation analyses further support these findings. For policymakers, our findings underscore the importance of fostering alignment between government and cultural tightness to enhance innovation policy effectiveness, especially in the post-MEI context. This national innovation initiative established a unified innovation goal, shifting the landscape for local policy impacts. Post-MEI, rather than simply intensifying innovation emphasis, a more effective approach may involve calibrating policies to local cultural contexts and institutional conditions, especially in regions with high cultural and governmental tightness, where institutional pressures are already strong.